Perencanaan dan Pengendalian Persediaan Bahan Baku Benang dengan Lot Sizing Economic Order Quantity - Christian Lois; Janny Rowena; Hendy Tannady (Universitas Bunda Mulia, 2017)
The object of this study is the inventory system of manufacturing companies with sock products in Tangerang, Banten. Types of socks produced are plain white socks, black socks, and small socks. This study aims to determine the description of the planning and control of raw material inventory and find out how much raw materials to be prepared as well as the total cost of production produced by applying the method of Material Requirement Planning from the production process. In its production activities, the company uses 4 main raw materials making white socks namely Polyester White yarn, Spandex, Nylon, and Rubber. In one day, production produces 3 dozen socks. The raw materials used are 1 cone yarn for 2.5 dozen. So to produce 3 dozen socks a day, it takes 1.2 cone threads. From the analysis, it is known that the booking fee is Rp.28000 per message and the storage fee is Rp.2000 per unit per year. Thus the value of economic needs or Economic Order Quantity generated is 157 units. Thus, for Polyester White yarn material (75%) requires 47.1 cones, Spandex yarn (15%) requires 9,42 cones, nylon yarn (5%) and rubber yarn (5%) equally require 3.14 cone. Set up fee Rp.156586 while the storage fee Rp.157000 so the total cost Rp.313586.Keywords: Socks, Material Requirement Planning, Economic Quantity